The cell-type specific uptake of polymer-coated or micelle-embedded QDs and SPIOs does not provoke an acute pro-inflammatory response in the liver - Heine, Markus; Bartelt, Alexander; Bruns, Oliver T.; Bargheer, Denise; Giemsa, Artur; Freund, Barbara; Scheja, Ludger; Waurisch, Christian; Eychmüller, Alexander; Reimer, Rudolph; Weller, Horst; Nielsen, Peter; et al. (Beilstein Journal of Nanotechnology, 2014)
Semiconductor quantum dots (QD) and superparamagnetic iron oxide nanocrystals (SPIO) have exceptional physical properties that are well suited for biomedical applications in vitro and in vivo. For future applications, the direct injection of nanocrystals for imaging and therapy represents an important entry route into the human body. Therefore, it is crucial to investigate biological responses of the body to nanocrystals to avoid harmful side effects. In recent years, we established a system to embed nanocrystals with a hydrophobic oleic acid shell either by lipid micelles or by the amphiphilic polymer poly(maleic anhydride-alt-1-octadecene) (PMAOD). The goal of the current study is to investigate the uptake processes as well as pro-inflammatory responses in the liver after the injection of these encapsulated nanocrystals. By immunofluorescence and electron microscopy studies using wild type mice, we show that 30 min after injection polymer-coated nanocrystals are primarily taken up by liver sinusoidal endothelial cells. In contrast, by using wild type, Ldlr-/- as well as Apoe-/- mice we show that nanocrystals embedded within lipid micelles are internalized by Kupffer cells and, in a process that is dependent on the LDL receptor and apolipoprotein E, by hepatocytes. Gene expression analysis of pro-inflammatory markers such as tumor necrosis factor alpha (TNFα) or chemokine (C-X-C motif) ligand 10 (Cxcl10) indicated that 48 h after injection internalized nanocrystals did not provoke pro-inflammatory pathways. In conclusion, internalized nanocrystals at least in mouse liver cells, namely endothelial cells, Kupffer cells and hepatocytes are at least not acutely associated with potential adverse side effects, underlining their potential for biomedical applications.
Keywords: hepatocytes; inflammation; Kupffer cells; liver sinusoidal endothelial cells; nanoparticle toxicity; nanoparticle uptake; quantum dots; superparamagnetic iron-oxide nanocrystals